2024
DOI: 10.17309/tmfv.2024.1.04
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Motor Skills and Motivation to Learn Physical Education Through the Use of Traditional Games

Hilmy Aliriad,
Adi S,
Jujur Gunawan Manullang
et al.

Abstract: Study purpose. This study aims to investigate motor skills and motivation to learn physical education through traditional games. Materials and methods. The study was conducted using an experimental method and involved 60 students from primary schools in Purwodadi District, Grobogan Regency, Indonesia. Data were collected by measuring motor skills and learning motivation through affective, cognitive and psychomotor tests that were examined for validity and reliability. In addition, students' character was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…These findings are consistent with previous research indicating that fun and interactive learning approaches can effectively facilitate the development of motor skills in elementary school students (Rizqi & Sutapa, 2019). The study found that using games and physical activities in learning can enhance children's gross motor skills (Aliriad et al, 2024;Nur et al, 2020;Sutapa & Suharjana, 2019). Similarly, research results have shown that integrating gaming elements into learning can improve coordination and motor control in elementary school students (Mujriah et al, 2022;Saputra et al, 2021;Suryadi et al, 2023).…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with previous research indicating that fun and interactive learning approaches can effectively facilitate the development of motor skills in elementary school students (Rizqi & Sutapa, 2019). The study found that using games and physical activities in learning can enhance children's gross motor skills (Aliriad et al, 2024;Nur et al, 2020;Sutapa & Suharjana, 2019). Similarly, research results have shown that integrating gaming elements into learning can improve coordination and motor control in elementary school students (Mujriah et al, 2022;Saputra et al, 2021;Suryadi et al, 2023).…”
Section: Discussionsupporting
confidence: 91%
“…The stage is given with 3 distances, namely 10 metres, 20 metres and 30 metres with a frequency of exercise in a week as much as 4 times treatment and a total of 14 sessions including pre-test at the beginning and post-test results of research to determine the minimum score and final results of athletes. After the treatment of the drill method on athletes, it is found that there are influences that arise, one of which is the increase in the results of athletes training (Aliriad et al, 2024;Hendker & Eils, 2021). The increase in score also led to an increase in the athlete's confidence in archery to produce a consistent technique (Alfindo & Sasmarianto, 2023).…”
Section: Discussionmentioning
confidence: 99%